2023
DOI: 10.1136/bmjopen-2022-067348
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with the number of children ever born by married Ghanaian females: a cross-sectional analysis

Abstract: ObjectiveMost studies in Ghana on determinants of children ever born (CEB) are often conducted among all females of reproductive age and do not adequately report patterns among married females. Considering the importance of marriage to fertility in the Ghanaian context, this study seeks to explore the association of socioeconomic characteristics of married Ghanaian women with CEB.DesignData from the 2017 Ghana Maternal Health Survey were used. Three separate models were considered: linear regression model usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…In sub-Saharan Africa, Kebede et al (2022) reported that women with a low level of education had the highest desired fertility. Boateng et al (2023) showed that in Ghana, married women with higher levels of education had fewer children. Zenebe-Gebre (2020) revealed that education has a negative effect on female fertility in Malawi.…”
Section: Women's Educationmentioning
confidence: 99%
“…In sub-Saharan Africa, Kebede et al (2022) reported that women with a low level of education had the highest desired fertility. Boateng et al (2023) showed that in Ghana, married women with higher levels of education had fewer children. Zenebe-Gebre (2020) revealed that education has a negative effect on female fertility in Malawi.…”
Section: Women's Educationmentioning
confidence: 99%
“…Marriage age is not only been linked with the declined fertility in Europe and North America, but has been identified as one explanations to the high fertility levels observed In Africa and Asia where early marriages is still a common practice [ 15 ]. In the developing world, the main purpose of marriage is to have children which leads to early childbearing in women who marries at a younger ages [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides education, other influential variables of AFM are wealth index, religion, region of stay, and husband's education (Zahangir & Nahar, 2021). Boateng et al (2023) highlighted the significance of marriage to fertility in Ghana. Singh et al (2023) highlighted the necessity of raising the legal age of marriage for females from 18 years old.…”
Section: Introductionmentioning
confidence: 99%